Thermodynamic analysis of reactions in the system Al2O3–SiO2–CaO–P2O5 - Харыбина, Юлия Вячеславовна (Technology audit and production reserves, 2016)
The object of the research is identification of the coexisting phases in the system Al2O3–SiO2–CaO–P2O5. To achieve this aim it is necessary to use the thermodynamical method. This method allows to study the physical and chemical processes in the system Al2O3–SiO2–CaO–P2O5. Output thermodynamic data are calculated in the article: enthalpy ΔHo298, entropy So298, dependence formula of heating capacity from temperature Cp = f(T) for some combinations of system Al2O3–SiO2–CaO–P2O5, by different methods. This is important for carrying out thermodynamic analysis of phase equilibriums in this system. An opportunity of coupled reactions is determined. It is indicated about restructuring of conodes in the researching system. Knowledge of the structure of this system (due to the thermodynamical data) will allow to predict the phase transformations in the process of obtaining new refractory products.